2010
DOI: 10.1243/13506501jet787
|View full text |Cite
|
Sign up to set email alerts
|

Micro-geometry effects on the sliding friction transition in elastohydrodynamic lubrication

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 26 publications
0
51
0
Order By: Relevance
“…First, operating conditions and lubricant rheology parameters are entered along with representative measured 3D topography maps of both contacting surfaces. A fast, isothermal non-Newtonian (Eyring) mixed lubrication model described in [28] is used to calculate the stress history per load cycle of each surface point by solving the problem at different time steps as the surfaces slide-roll against each other. This fast approach to modelling micro-elasto-hydrodynamic lubrication (micro-EHL) conditions determines the clearance between the mating surfaces and the pressure fluctuations arising from the passage of roughness asperities through the contact in mixed lubrication conditions.…”
Section: Modelling Methodsmentioning
confidence: 99%
“…First, operating conditions and lubricant rheology parameters are entered along with representative measured 3D topography maps of both contacting surfaces. A fast, isothermal non-Newtonian (Eyring) mixed lubrication model described in [28] is used to calculate the stress history per load cycle of each surface point by solving the problem at different time steps as the surfaces slide-roll against each other. This fast approach to modelling micro-elasto-hydrodynamic lubrication (micro-EHL) conditions determines the clearance between the mating surfaces and the pressure fluctuations arising from the passage of roughness asperities through the contact in mixed lubrication conditions.…”
Section: Modelling Methodsmentioning
confidence: 99%
“…This can be accomplished by iteratively solving the system (3) and Eq. (8), similarly to the algorithm of Morales-Espejel et al [29]. However, it was found to be timeconsuming and a different single-loop approach was developed, which is described in Appendix 2.…”
Section: Numerical Lubrication Modelmentioning
confidence: 99%
“…Multilevel multi-integration was used to facilitate the calculations. A load-sharing concept-based approach which employs the half-space theory was also implemented by Morales-Espejel et al [29]. They used Hertz' theory [23] to calculate the average pressure, and the mean film thickness was obtained from ''central film thickness formula,'' such as the Dowson and Higginson fit [10] be it with the extension of an equivalent roughness using the perturbation method.…”
Section: Introductionmentioning
confidence: 99%
“…Friction calculations in mixed lubrication frequently combine models for boundary lubrication and fluid-film conditions. Morales-Espejel et al 16 and Popovici and Schipper 17 have published approaches for deterministic microcontact models and Eyring fluids.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] In this article, the Carreau equation is considered, bearing in mind that Jang et al, 20 Chapkov et al 21 and Liu et al 22 have reported an extensive set of numerical solutions and comparisons with experiments, which reveal that the Carreau model properly characterises the shear-thinning effects, in particular for the case of the mineral base and the polyalphaolefin lubricants [23][24][25] used in this work. Concerning the mixed lubrication analysis, unlike models based on the detailed geometry of the asperities 16,17 which generally complicate the use of analytical or semi-analytical algorithms, we use a macroscopical approach that only requires the use of a standardised statistical roughness parameter. In this way, we aim for an approach even more simplified than the aforementioned models, in order to develop a fully analytical model.…”
Section: Introductionmentioning
confidence: 99%